Factors influencing turnover intention among employees at HRSB company / Nur Syafiqah Abdullah - Abdullah, Nur Syafiqah (Faculty of Business and Management, 2019)
Nowadays, employee’s turnover is considered as one of the challenging issues and problems in business or organization. It is difficult and huge challenge for Human resource managers to retain the employees for longer period of time and this issue become continuous problems that plagued the company particularly in reference to Malaysia. The objective of this study is to explore the factors that influencing turnover intention among employees at headquarter (HQ) of HRSB Company as well as to identify the most significant factors influencing the turnover intention. Three independent variables namely job satisfaction, job stress and work-life balance were examined to determine their relationship with dependent variable which is turnover intention. Data was collected through questionnaire from 51 respondents working in this company using a convenience sampling technique. Data obtained has been analysed using Statistical Package for Social Science (SPSS) version 22. Descriptive statistic, correlation, and regression analysis were used in this study for the purposes to find out the relations between the variables. From the results, job satisfaction is found having negative but significant relationship with turnover intention. While for job stress is found having positive and significant relationship with turnover intention and only work-life balance is found having positive but not significant. Hence in multiple regression showed that two factors are related to turnover intentions, and consistent with other researcher findings.